ANALISIS PERKEMBANGAN TEORI SEBAGAI LANDASAN PENGEMBANGAN ILMU PENGETAHUAN - Nurazizah, Naeila; Yanti, Olpy Nopy; Harbi, Harkat Aulia; Tukijo, Tukijo; Surato, Surato; Sobirin, Sobirin (STKIP Subang, 2026)
In the context of rapid change, especially in the digital and global era, the development of theory becomes essential to maintain the relevance of scientific knowledge. Theory is not only a collection of ideas but also a systematically tested framework used to explain, predict, and interpret various phenomena in human life. This study aims to analyze the development of theory as a foundation for the advancement of science. The research uses a qualitative approach with a library research method by examining various relevant scientific literatures. The results show that theory plays a fundamental role as a conceptual framework, analytical tool, and guide in scientific thinking. The development of theory occurs dynamically through paradigm shifts, technological advancements, and interdisciplinary integration. However, theories also have limitations, especially when they are rigid and unable to adapt to new phenomena. In the modern digital era, the development of theory faces complex challenges, including rapid technological change and emerging global issues. Therefore, adaptive, flexible, and ethically grounded theories are needed to ensure their relevance and contribution to solving societal problems. This study concludes that theory remains a crucial foundation in the development of science and acts as a bridge between abstract knowledge and empirical reality.